Pondok Pesantren: changes and its future - Gamal Abdul Nasir Zakaria, (Faculty of Education, Universiti Kebangsaan Malaysia, 2010)
The tradition of education at Pondok Pesantren in Indonesia and in the Malay world possesses a long history and represents a portion of the history of the growth and spread of Muslims in the region. Pondok Pesantren is not only associated with the meaning of Islam but also incorporates the symbol of authenticity of the Malay community. This educational institution functions as an organization for the study of religious knowledge, preserves Islamic traditions, and produces both Muslim scholars as well as leaders. Pondok Pesantren, during its long history, has successfully proven itself to be an Islamic educational institution which is prestigious, of quality and self-supporting. Although its existence has not been influenced by sociopolitical, economical or cultural changes, this does not mean that Pondok Pesantren does not face problems and challenges, be they internal or external ones. This paper will discuss some issues such as the survival of Pondok Pesantren today and in the future with the fast-paced challenges which are happening around us.